1979
DOI: 10.1159/000112439
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sciatic Nerve Protein Composition during Postnatal Development of Mice

Abstract: Proteins from whole nerve were visualized on a SDS-PAGE system and compared to known proteins enriched in various subcellular tissues during nerve development in mice. Whole nerve samples avoid the a priori assumptions that the immature and mature biophysical characteristics of nerve tissues remain the same during nerve development. Total protein, nerve lengths and wet weights were recorded so that protein recovery and the relative amounts of specific protein species could be quantified. Electrophoretic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
(35 reference statements)
3
5
0
Order By: Relevance
“…Our finding of a developmental change in proportions of the main basic proteins, with an increase of the smaller one (P,) relative to the larger (PI), corroborates the report of Groswald and Luttges (1979), who found a progressive accumulation of small basic protein in mouse sciatic nerve for 50 days postpartum. Basic proteins seem to change similarly in rats: Wiggins et al (1975) showed a relative increase in P, (designated P:!…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding of a developmental change in proportions of the main basic proteins, with an increase of the smaller one (P,) relative to the larger (PI), corroborates the report of Groswald and Luttges (1979), who found a progressive accumulation of small basic protein in mouse sciatic nerve for 50 days postpartum. Basic proteins seem to change similarly in rats: Wiggins et al (1975) showed a relative increase in P, (designated P:!…”
Section: Discussionsupporting
confidence: 92%
“…The available evidence appears, however, to argue for a straightforward effect on myelin protein composition. This can be seen in the studies of Wiggens et al (1975) and Groswald and Luttges (1979), which have used whole nerves and which have shown variations in basic proteins similar to those we have obtained with isolated myelin. Our more recent studies (Greenfield et al, 1983) have also shown that the age/mutation-related changes in P, are found in analyses of whole nerves from YQ and old Qk and control mice.…”
Section: J Wezse Et Alsupporting
confidence: 79%
“…However, the ratio between the small and the large compo nent of MBP increased in both control and mid mice. This developmental change was previously reported in the PNS [14,[33][34][35] and in the CNS [1-3, 6. 21,27].…”
Section: Discussionsupporting
confidence: 84%
“…The increased proportion of the higher M, forms of MBP in quaking CNS is also apparent in the immunoblot of whole brain homogenate shown by Sorg et al (1986), although it is not mentioned in the results. During normal development of the mouse CNS and PNS, the proportion of the 14K MBP in myelin increases relative to the larger froms of MBP (Barbarese et al, 1978;Groswald and Luttges, 1979;Weise et al, 1983). Therefore, the greater proportions of the higher M, forms of MBP in quaking brain and nerve probably reflect the immaturity of the myelin in this mutant.…”
Section: Discussionmentioning
confidence: 90%